KOLABORASI PENDIDIKAN FORMAL DAN VOKASIONAL DI SEKOLAH LUAR BIASA IBNU ISMAIL BATAM (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This School Field Introduction Activity Was Carried Out With The Title "Collaboration Of Formal And Vocational Education At Ibnu Ismail Special School Batam." The Main Purpose Of This Educational Collaboration Is To Provide Insight To Students With Disabilities Background About Basic Knowledge Such As Reading, Writing, Arithmetic As Well As Basic Islamic Religious Education Combined With Vocational Education Focused In The Field Of Convection Such As Sewing, Cutting Cloth, Measuring Patterns. This Educational Activity Was Carried Out At Ibnu Ismail Special School Batam Which Is Located In Kda Housing Batam Center Cluster Nuri - Kepodang. In Addition To That Another Purpose Of Collaboration Of Formal And Vocational Education Is To Prepare Students In A More Independent Life In The Future And Have Competitiveness. The applied method is hands-on practice with intensive mentoring, verbal and hands-on explanations, and gradual guidance to facilitate students' understanding of new concepts. The results of the collaboration show that students are able to produce simple works, demonstrate increased creativity, self-confidence, opportunities for independent entrepreneurship, and psychosocial therapy support. Although there are several obstacles such as limited vision, difficulty concentrating, limited time, and limited additional facilities and infrastructure, these limitations can be minimized through mentoring strategies, material adjustments, and ongoing motivation. Thus, this collaborative method not only provides knowledge and practical skills for people with disabilities, but also opportunities for economic empowerment and improved well-being through independent skills-based entrepreneurship.